Answer:
-1078
Explanation:
n=0 is the first term in the sequence.
Every next term is 20 less then the previous term.
In Mathematics you can write this as follows:
f(n) = f(0) - (n-1)*20
f(n) = f(0) - {(n-1)*20}
f(n) = f(0) - {(20n) -20}
Attention: Please note that -1 * -20 = +20
f(n) = f(0) - 20n + 20
Check yourself, find f(2):
f(0) = 2
f(2) = 2 - 20*2 + 20
f(2) = 2 - 40 + 20
f(2) = 2 - 20
f(2) = -18
Check yourself once more, find f(3):
f(0) = 2
f(3) = 2 - 20*3 + 20
f(3) = 2 - 60 + 20
f(3) = 2 - 40
f(3) = -38
Now just find f(55):
f(55) = 2
f(55) = 2 - 20*55 + 20
f(55) = 2 - 1100 + 20
f(55) = 2 - 1080
f(55) = -1078